Hubungan Supervisi dan Motivasi Dengan Kepatuhan Perawat Mencuci Tangan Di RSUD - Danuarsa Parwa; Menik Sri Krisnawati; Emy Darma Yanti (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2019)
Health-care Associated Infection (HAIs) is a serious health problem and impact the country's economic burden. The efforts of hand wash is to prevent HAIs. Head of Space supervision and nurse’s motivation factors are affect hand washing compliance that remain poor among nurses. This research was conducted to determine the relationship between Head of Space supervision and nurse’s motivation with hand washing compliance in RSUD Y in 2018. This research was descriptive correlation with cross sectional design. The samples were 33 associate nurse through total sampling. The data was collected by questionnare and observation sheet. This research showed there is relationship between Head of Space supervision with hand washing compliance (p-value = 0.014, r = 0.423) and there is relationship between nurse’s motivation with hand hygiene compliance (p- value = 0.012, r = 0.433). This research concluded were Head of Space supervision by doing bad will decreased hand hygiene compliance and if nurse’s motivation increases will increased hand hygiene compliance among nurses in X room RSUD